2022
DOI: 10.1186/s13054-022-04189-5
|View full text |Cite
|
Sign up to set email alerts
|

Delivery decision in pregnant women rescued by ECMO for severe ARDS: a retrospective multicenter cohort study

Abstract: Background Although rarely addressed in the literature, a key question in the care of critically pregnant women with severe acute respiratory distress syndrome (ARDS), especially at the time of extracorporeal membrane oxygenation (ECMO) decision, is whether delivery might substantially improve the mother’s and child’s conditions. This multicenter, retrospective cohort aims to report maternal and fetal short- and long-term outcomes of pregnant women with ECMO-rescued severe ARDS according to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…After the elimination of studies not relevant to the subject of interest and meeting abstracts, 25 were retrieved for complete analysis. 4,6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Four studies were excluded: three for including duplicate patients published in other included articles [40][41][42] and one because of the inability to determine from published information the number of women with maternal mortality. 43 The corresponding authors for the latter study were contacted and indicated that they could not provide the additional information requested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the elimination of studies not relevant to the subject of interest and meeting abstracts, 25 were retrieved for complete analysis. 4,6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Four studies were excluded: three for including duplicate patients published in other included articles [40][41][42] and one because of the inability to determine from published information the number of women with maternal mortality. 43 The corresponding authors for the latter study were contacted and indicated that they could not provide the additional information requested.…”
Section: Resultsmentioning
confidence: 99%
“…Eight corresponding authors from included studies were contacted, with all providing additional supplementary data for inclusion in either the primary or secondary analyses. 6,25,32,33,[35][36][37]39 The study by Barrantes et al 38 included two patients who were also included in the study by Byrne et al 6 These two patients' clinical information was excluded from the reported outcomes of the Barrantes et al 38 study when analyzed for the pooling of results. In total, 21 studies with 386 pregnant individuals who had critical COVID-19 managed with ECMO were included in the review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the authors’ experience, timing of delivery is dictated if the fetal prognosis is favorable based on gestational age and after a multidisciplinary consensus that delivery can improve maternal respiratory status. Pregnant patients on ECMO are more likely to delivery via cesarean delivery in nearly two thirds of cases 18 . Vaginal delivery is not contraindicated but if delivery is indicated but the patient may be too critically ill to undergo an induction of labor leaving cesarean delivery as the safest option.…”
Section: Delivery Timing and Mode Of Deliverymentioning
confidence: 99%
“…Vaginal delivery is not contraindicated but if delivery is indicated but the patient may be too critically ill to undergo an induction of labor leaving cesarean delivery as the safest option. 18 Considerations include the patient’s pulmonary and cardiovascular stability and their ability to tolerate an induction of labor. If delivery is indicated for maternal or fetal reasons, allowing time for induction of labor may not be optimal.…”
Section: Delivery Timing and Mode Of Deliverymentioning
confidence: 99%